Rates of Preterm Birth and Low Birth Weight in an Adolescent Obstetric Clinic: Achieving Health Equity Through Trauma-Informed Care (Mary Ann Liebert, 2023)
Objectives: Adolescents who are pregnant and identify as Black are exposed to more societal harms that increase their and their offspring's risk for poor health outcomes. The Colorado Adolescent Maternity Program (CAMP) offers comprehensive, multidisciplinary (medical, behavioral health, nutrition, case management), trauma-informed obstetric care to pregnant adolescents to ensure the healthiest pregnancy and birth possible and pursue health equity. The present study aimed to examine ethnic and racial disparities in preterm birth and low birth weight before and after implementation of a trauma-informed model of care. Methods: Participants were 847 pregnant adolescents (ages 12?22 years; 41% self-identified as Hispanic, 32% as non-Hispanic Black, 21% as non-Hispanic white) who received prenatal treatment-as-usual (TAU) or trauma-informed treatment. Demographic information, mental health symptoms, and birth outcomes were abstracted from medical records. Results: Overall, findings provided support that implementation of a trauma-informed model of prenatal care led to equitable birth outcomes across racial and ethnic groups. Specifically, Black adolescents in the TAU group were more than twice as likely to deliver preterm or low birth weight infants compared with white and Hispanic adolescents. In the trauma-informed group, however, there were no statistical differences in birth outcomes across racial/ethnic groups, indicating an elimination of disparities in both preterm birth and low birth weight in this population. These more equitable birth outcomes occurred even in the context of adolescents of color having reported more severe depression symptoms postimplementation. Conclusions: These findings provide evidence that a health system-level intervention, herein trauma-informed obstetric care for adolescents, can play a meaningful role in the reduction of racial disparities in birth outcomes.